Sense or Nonsense?: New Zealand Heritage Leglislation in Perspective - Greg Vossler (Public History Review, 2006)
This article provides an overview of the current legislative ‘landscape’ that shapes the nature of historic heritage protection and management in New Zealand. It identifies some of the principal laws that impinge on historic heritage and outlines the purpose and principles, administrative processes, protective measures and offences and enforcement provisions associated with each of these statutes.